Iron deposition heterogeneity in extrapyramidal system assessed by quantitative susceptibility mapping in Parkinson’s disease patients with type 2 diabetes mellitus - Li, Wanyao; Gao, Bingbing; Du, Wei; Jiang, Yuhan; Yang, Jing; Hu, Rui; Liu, Yangyingqiu; Liu, Na; Zhang, Yukun; Song, Qingwei; Miao, Yanwei (Frontiers in Aging Neuroscience, 2022)
Purpose Excessive brain iron depositions were found in both patients with Parkinson’s disease (PD) and those with type 2 diabetes mellitus (T2DM). The present study aimed to explore iron deposition and heterogeneity in the extrapyramidal system in PD patients with T2DM using quantitative susceptibility mapping (QSM) and further to reveal the effect of T2DM on the changes in brain iron in patients with PD. Materials and methods A total of 38 PD patients with T2DM (PDDM), 30 PD patients without T2DM (PDND), and 20 asymptomatic control subjects (CSs) were recruited for this study. All subjects underwent multiple MRI sequences involving enhanced gradient echo T2 star weighted angiography (ESWAN). The magnetic sensitivity values (MSV) and volume of the whole nuclei (MSVW, VW) and high iron region (MSVRII, VRII) were measured on the bilateral caudate nucleus (CN), the putamen (PUT), the globus pallidus (GP), the substantia nigra (SN), the red nucleus (RN) and the dentate nucleus (DN). Clinical and laboratory data were recorded, especially for the Hoehn and Yahr (H-Y) stage, the Montreal Cognitive Assessment (MoCA), the Mini-Mental State Examination (MMSE), the Hamilton Depression Rating Scale (HAMD), and the Hamilton Anxiety Rating Scale (HAMA). All QSM data were compared between PDDM and PDND groups and correlated with clinical and laboratory data. Results Compared to the PDND group, the VRII/VW of the left CN was significantly increased in the PDDM group. Significantly higher MSVW and MSVRII were also found in the PDDM group, including bilateral SN of MSVW, right PUT, and bilateral CN, GP, and SN of MSVRII. The H-Y stage of the PDDM group was significantly higher than that of the PDND group. The MSVRII of bilateral RN of the PDDM group was positively correlated with the HAMA scores. HDL, DBP, and SBP levels were associated with MSVRII of right CN in the PDDM group. Conclusion T2DM could aggravate the disease severity and anxiety in patients with PD. The iron distribution of deep gray matter nuclei in PD patients with T2DM was significantly heterogeneous, which was related to blood pressure and blood lipids.